TINGKAT PENERIMAAN KONSUMEN TERHADAP BAKSO IKAN LELE DENGAN KONSENTRASI DAGING YANG BERBEDA - Musdalifah, Musdalifah; Tanod, Wendy Alexander (KAUDERNI : Journal of Fisheries, Marine and Aquatic Science, 2016)
Increased production of catfish in Central Sulawesi was not followed by an increase in the consumption of meat catfish. Diversification of products made from meat catfish, into attractive products such as meatballs need to be done. This study aims to determine consumer acceptance of meatball use catfish meat. This study uses 4 treatments and 3 repetitions. The parameters tested in each treatment, the ash content, moisture content and organoleptic assessment. The treatments were given, namely variations in the concentration of meat catfish 200 g, 400 g, 600 g and 800 g. The results showed the ash content meatballs catfish ranging from 0.64% to 0.93%. The water content meatball catfish of each treatment ranged between 66.75% - 70%. Value organoleptic appearance meatballs catfish range of 6.33 to 6.83. Smell value of meatballs catfish ranging from 6.50 to 6.83. Flavor value of meatballs catfish ranging from 6.33 to 6.83. Texture value of meatballs catfish ranging from 6.33 to 6.83. From the results of this study concluded that the levels of ash and water content meatball catfish from each treatment were given still meet the Indonesian National Standard and meatballs catfish with meat concentrations of 600 g and 800 g preferably panelists